Dry sliding wear and friction performance of zirconium dioxide tribopairs - Bailey, Richard; Sun, Yong (Frontiers in Coatings, Dyes and Interface Engineering, 2024)
Zirconium is an attractive engineering material owing to its commendable temperature, corrosion resistance, and excellent biocompatibility. Despite these merits, its industrial applicability is hindered by elevated wear and friction in tribological settings. Previous research has concentrated on unmatched pair contacts involving zirconium and alumina primarily due to the exceptional hardness. However, there is a noticeable dearth of literature on the matched pair contact condition for zirconium dioxide. Thermal oxidation is a promising and cost-effective method to address the suboptimal tribological performance and enhance the mechanical and electrochemical properties of zirconium. In this study, thermal oxidation is employed to produce a 6-μm-thick oxide layer in an air furnace at 650°C for 6 h. Subsequently, the resulting surface coating was tribologically tested using a pin-on-disc tribometer against two distinct counterface materials, namely, alumina and zirconium dioxide, in a dry and unlubricated environment. The findings reveal that matched contact between the zirconium dioxide tribopair is unfavorable, leading to elevated friction and wear rates. Consequently, this configuration should be avoided in dry contact situations characterized by high contact pressures. However, under lower contact pressures, the wear performance is acceptable. Furthermore, when combined with lubrication, this system may have potential applications in bio-tribological systems.